Asymmetric Hybrid Polyoxometalates: A Platform for Multifunctional Redox‐Active Nanomaterials. Issue 50 (24th October 2019) - Hampson, Elizabeth; Cameron, Jamie M.; Amin, Sharad; Kyo, Joungman; Watts, Julie A.; Oshio, Hiroki; Newton, Graham N.
Abstract: Access to asymmetrically functionalized polyoxometalates is a grand challenge as it could lead to new molecular nanomaterials with multiple or modular functionality. Now, a simple one‐pot synthetic approach to the isolation of an asymmetrically functionalized organic–inorganic hybrid Wells–Dawson polyoxometalate in good yield is presented. The cluster bears two organophosphonate moieties with contrasting physical properties: a chelating metal‐binding group, and a long aliphatic chain that facilitates solvent‐dependent self‐assembly into soft nanostructures. The orthogonal properties of the modular system are effectively demonstrated by controlled assembly of POM‐based redox‐active nanoparticles. This simple, high‐yielding synthetic method is a promising new approach to the preparation of multi‐functional hybrid metal oxide clusters, supermolecular systems, and soft‐nanomaterials. Abstract : A one‐pot approach to the isolation of an asymmetrically functionalized organic–inorganic hybrid Wells–Dawson polyoxometalate is presented. The cluster bears two organophosphonate moieties with contrasting physical properties: a chelating metal‐binding group and a long aliphatic chain unit that facilitates solvent‐dependent self‐assembly into soft redox‐active nanostructures.